Transformational leadership in Islamic education: The role of madrasa principals in enhancing teacher religiosity - Dzul Fiqri; Muhaemin; Rukmana R. Said (At Turots: Jurnal Pendidikan Islam, 2025)
This study aims to analyze the principal’s leadership strategy in developing religiosity values at Madrasahh Aliyah Salumakarra, Bua Ponrang District, Luwu Regency. The primary focus of this research is to identify the strategies employed by the madrasah principal in enhancing teachers’ religiosity, understand the process of internalizing religious values in teaching, and explore the supporting and inhibiting factors in implementing these strategies. This research employs a qualitative approach with a descriptive-analytical method. Data sources consist of primary and secondary data collected through observations, in-depth interviews, and document analysis. Pedagogical, psychological, and sociological approaches are applied to analyze the relationship between the madrasah principal’s leadership and the development of religiosity values in the educational environment. The findings indicate that the madrasah principal employs various strategies to enhance teachers’ religiosity. These strategies include (1) role modeling, where the principal sets an example in worship and Islamic behavior, (2) habit formation, which establishes a religious culture through routine activities such as dhuha prayer, dhikr, collective supplications, and Quran recitation before lessons, (3) partnerships, involving collaboration with parents, religious figures, and the community to foster a religious environment, (4) internalization of Islamic values, where moral and ethical teachings are integrated into the curriculum, and (5) guidance and mentoring, which includes motivation and spiritual reinforcement for teachers and students to strengthen their faith and devotion. Teachers’ religiosity at the madrasah is reflected in various aspects of their daily lives, including adherence to religious practices, mutual support, and the application of Islamic values in social interactions. Moreover, teachers are expected to emulate the qualities of the Prophet Muhammad (Shiddiq – truthfulness, Tabligh – conveying the truth, Amanah – trustworthiness, and Fathonah – wisdom). Supporting factors in strengthening religious values include institutional support from the madrasah, active student participation, and a conducive social environment for religious practice. However, several inhibiting factors persist, such as a lack of religious awareness among some teachers and inadequate facilities, including limited prayer spaces and insufficient Islamic learning media.The study concludes that the principal’s leadership plays a crucial role in fostering a religious culture in the madrasah. Effective leadership strategies can reinforce religious values in education for both teachers and students. Therefore, the key recommendations from this research include increasing teachers’ awareness of religiosity, strengthening religious development programs, and providing better facilities to support the optimal implementation of Islamic values in the madrasah.